Polyploid and Hybrid Genomics - Chen, Z. Jeffrey; Birchler, James A. (James Arthur), 1950- (Chicester : Wiley, 2013)
Polyploidy plays an important role in biological diversity, trait improvement, and plant species survival. Understanding the evolutionary phenomenon of polyploidy is a key challenge for plant and crop scientists. This book is made up of contributions from leading researchers in the field from around the world, providing a truly global review of the subject. Providing broad-ranging coverage, and up-to-date information from some of the world's leading researchers, this book is an invaluable resource for geneticists, plant and crop scientists, and evolutionary biologists.
Includes bibliographical references and index.
Print version record.
Keywords: Polyploidy; Hybrid vigor; Hybridization, Genetic; Hybridization; Polyploidy; Electronic books